Influence of Site Curing on Bond Properties of Reinforced Lightweight Concrete - Mohammad, Abdul Mannan; Teo, Delsye Ching Lee; Kurian, V. J. (African Journals Online (AJOL), 2006)
An experimental investigation on structural lightweight concrete was conducted using oil palm shell (OPS) as coarse aggregate, which is a type of solid waste discarded in large quantities in palm oil mills. The compressive strength and the pull-out bond strength were determined in this study for up to 28 days under three curing conditions. These include two currently practiced site curing conditions and one laboratory full water curing. The full water curing condition was considered as controlled curing. The obtained 28-day air-dry density, compressive strength and pull-out strength were in the range of 1930-1995 kg/m3 , 25-28 MPa and 5.4-9.4 MPa respectively which satisfied the requirements for structural lightweight concrete. The developed compressive strength and pull-out strength under both site curing conditions were relatively lower than full water curing condition but still were higher than minimum requirement as per standard.